Pengajian Berbasis TPQ (Taman Pendidikan Al-Quran) bagi Pendidikan Anak untuk Meningkatkan Potensi Desa Gambiran - Aisa, Aufia; Anam, Moh Khoirul; Hidayah, Nurul; Al-Ghozali, M.Dzikrul Hakim; Veri, Achmad Riyan; Rozaki, M Iftakhur; Adawiyah, Robiatul; Andani, Dita Dwi Cahya Andani (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2024)
One of the efforts to increase the understanding of the people of Gambiran Village from a religious perspective is that the service program is holding a "Recitation Based on the Importance of TPQ (Al-Qur'an Education Park) for Children's Education" which is expected to help strengthen the management of children's education and make the village's potential better and quality. The approach method in this service activity uses Community Based Research. The parties involved in this recitation were members of the general public, especially Jam'iyah Yasin Tahlil women in the Ngrowo Hamlet area, Gambiran Village, with a total of 58 participants, and Mr. H. Moh. Khoiril Anam, S.H.I, M.Pd.I as the lecturer. The method of implementing this activity uses face-to-face methods in the form of recitation and socialization. The results after the study was conducted received a positive response, this can be proven by the community's satisfaction through and the addition of students studying at TPQ Al-Ikhsan, Ngrowo Hamlet, Gambiran Village after participating in the study.